The Psychology of Emotion Regulation: Strategies and Implications for Mental Well-being - Dr. Nidhi Bura (Innovative Research Thoughts, 2023)
Mental health depends on emotion management. Emotion management improves psychological health, resilience, and adaptation. This research examines emotion management methods and their effects on mental health. Antecedent-focused and response-focused techniques regulate emotions. Cognitive reappraisal or scenario selection are antecedent-focused procedures that alter the emotional experience. Reaction-focused methods, like expressive suppression or emotion suppression, modulate the emotional response after it occurs. Emotion control approach seems to affect mental health. Adaptive emotion regulation procedures like cognitive reappraisal promote psychological outcomes including anxiety and depression reduction, emotional well-being, and interpersonal connections. Reinterpreting a circumstance to change one's emotional reaction improves emotion management and psychological adjustment. Suppression and avoidance may harm mental health. Suppressing or ignoring emotions may bring short-term respite, but it may lead to emotional anguish, physiological arousal, and decreased interpersonal performance. These techniques limit emotional processing and expression, causing psychopathology and preventing adaptive coping.